(untitled) (Experimental biology, 2015)
In 2007, the government initiated a new ban on felling haloxylon for ten years. It can be concluded that the recovery is required for haloxylon . Existing technologies of cultivation of planting material requires considerable resources and manpower. Therefore necessary to develop the enabling technologies accelerate the availability of planting material,which could contribute to reforestation in the areas of human impact . The article presents the possibility of mass reproduction of (Haloxylon aphyllum) by biotechnological methods.